Polymorphism in the hypoxia-inducible factor 1alpha gene may confer susceptibility to LDD in Chinese cohort. - Wen-Ping Lin (Public Library of Science (PLoS), 2013)
Objective This study aimed to investigate whether or not hypoxia-inducible factor-1α (HIF-1α) gene variants are associated with the susceptibility and clinical characteristics of lumbar disc degeneration (LDD). Methods We examined 320 patients with LDD and 447 gender- and age-matched control subjects. We also determined the HIF-1α gene variants, including C1772T (P582S) and G1790A (A588T) polymorphisms. Results Significant differences were observed in allelic and genotypic distributions of 1790 A > G polymorphisms between LDD cases and control subjects. Logistic regression revealed that 1790 AA genotypes indicated a protective effect against the development of LDD. The HIF-1α 1790 A > G polymorphisms also affected the severity of LDD as evaluated based on the modified Japanese Orthopedic Association (mJOA) scores. The 1790 AA genotype carriers exhibited significantly lower mJOA scores than AG and GG carriers. C1772T did not show any association with the risk and severity of LDD. Conclusion Our study suggested that HIF-1α 1790 A > G polymorphisms may be used as a molecular marker to determine the susceptibility and severity of LDD.